Γ-Ray irradiation effect on GdBO3/silica:Ce3+ composite prepared by sol gel method. (September 2015) - Ladjouzi, S.; Tala-Ighil, R.; Iratni, A.; Izerrouken, M.; Guerbous, L.; Hadji, S.; Bensouici, F.; Pérez, F.J.
Abstract: Samples of GdBO3 doped with Ce 3+ embedded in amorphous silica matrix were obtained by sol gel process and heat-treat at 1000 °C for 2 h in argon atmosphere. After elaboration, the samples were irradiated with γ-rays using cobalt ( 60 Co) source in the dose range from 1 to 5 kGy. The irradiation effect of γ-rays on structural and optical properties of the synthesized samples were investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transforms infrared spectroscopy (FTIR) and photoluminescence spectroscopy. XRD and TEM-EDS results reveal that γ-ray irradiation reduces the crystallite size from 55 nm to 30 nm. It is found from FTIR study that the absorption bands intensity assigned to structural groups containing BO4 and BO3 units as well as the banding of Si–O–Si bond increases with γ-ray dose up to 4 kGy. While photoluminescence measurements show that the emission bands attributed to the 5 d → 4 F transition of Ce +3 ion intensity decreases, it is still significant even after irradiation to a dose of 5 kGy. From this results it is concluded that the γ-ray irradiation up to a dose of 5 kGy improve the structural and morphological quality of the synthesized GdBO3 /silica: Ce 3+ without altering significantly its luminescence properties. Highlights: GdBO3 /silica: Ce 3+ composite was successfully elaborated using the sol gel method. GdBO3 :Ce 3+ heat-treated at 1000 °C exhibit an oval shape with vaterite structure. γ-Ray irradiation reduces the GdBO3 :Ce 3+ crystallite size from 55 to 30 nm. The GdBO3 :Ce 3+ particles become more compact after γ- ray irradiation. The emission bands remain important even after irradiation up to a dose of 5 kGy.